Pendekatan Metode Ward And Peppard Untuk Perencanaan Strategis Sistem Informasi DISPERINNAKER Kota Salatiga - Shania Arum Destyarini; Andeka Rocky Tanaamah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
DISPERINNAKER of Salatiga City is a government agency engaged in the Industry and Manpower sector. Information systems and information technology (IS / IT) are tools to achieve success in supporting the success of the government's vision and mission in order to create a digital era government. However, currently not all of the business processes at DISPERINNAKER are supported by the use of IS / IT, so that the performance process has not been running effectively and efficiently. Therefore, a good and well-planned IS / IT strategic plan is needed. This study uses the Ward and Peppard method approach which consists of a SWOT analysis with the addition of the IFE and EFE matrices which are used to evaluate internal and external factors by looking at the main strengths, weaknesses, opportunities, and threats in the organization, Value Chain Analysis, Critical Success Method. Factors (CSFs) Based on the IT Balanced Scorecard, and Mc Farlan's Strategic Grid which will produce an overview of information system requirements, solutions, and information system strategy recommendations which can later be formulated as strategic planning for implementation plans that will be carried out within 4 (four) years which will come.